The maritime border conflict between Nicaragua and Colombia (2013)
Doctor Luis Bernardo Díaz raises the history of the dispute between Nicaragua and Colombia on the subject of maritime border disputes. In particular, can be seen a respect to the judgment of the International Court of Justice and a critique to the Colombian diplomatic service by the fledgling defense in the international courts, indicating the high figures from the public Treasury earned by the “experts”